RESEPSI AL-QUR’AN DALAM TRADISI SLAMETAN TORON PARAO MASYARAKAT PESISIR MADURA: Kajian Living Qur’an di Kepulauan Masalembu - Abd. Muhaimin; Faishal Khair; Abd. Mun’em (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2023)
Abstract This research will discuss the Koran that lives in coastal communities in Madura, specifically in the Masalembu archipelago, Sumenep. The living Quran study framework is used to explore the reception of the Koran at the functional level of fishing communities. This research uses a descriptive-analytic method with a discursive tradition approach. Questions to be answered: First, how is the reception of the Al-Qur'an by the Masalembu people in the Toron Parao slametan tradition? and second, how the discursive traditions are formed within it? The basis of the research is a field study whose data sources are obtained from interviews and observations, plus several literature reviews. From this goal, it will result; first, in the slametan toron parao tradition in Masalembu, the letters of the Koran used are closely related to the hope of safety, wealth, and avoidance of evil; secondly, a ritual leader (kiai) has a central role in the tradition and the community entrusts his role from generation to generation. Apart from that, people's belief in the magical side of the Koran forms a religious pattern for coastal people and Madurese in general. Keywords: Living Qur'an, Slametan Toron Prao, Madura Coast